Anti-colon Cancer Activity of Parkia javanica (Lamk.) Merr. Bark Extract: An In-vitro Study (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The Methanolic extract of Parkia javanica bark (MEPJB) was examined in vitro to see whether it has any cytotoxic or chemotherapeutic potential against the colon cancer cell lines HCT116 and SW480. Cell viability or proliferation assay and migration assay were performed, which showed significant results. The bark extract exhibited significant cytotoxic potential against both the colon cancer cell lines, and it also inhibited cell migration in a dose-dependent and time-dependent experiment. The IC₅₀ values of MEPJB on the HCT116 cell line for 24 hours, 48 hours, and 72 hours were 83.33 μg/mL, 37.5 μg/mL, and 34.37 μg/mL, respectively, whereas on the SW480 cell line, the IC₅₀ values were 87.5 μg/mL, 40 μg/mL and 31.25 μg/mL for 24 hours, 48 hours, and 72 hours respectively. However, IC₅₀ doses of MEPJB were inactive against the normal, healthy human fibroblast cell line. Cytotoxicity screening of 5-fluorouracil (5-FU), a commonly used drug in colon cancer treatment, was also done on both the colon cancer cell lines HCT116 and SW480, which showed much higher IC₅₀ than MEPJB after 24 hours, 48 hours, and 72 hours of incubation. MEPJB changed the cell morphology and induced apoptosis in colon cancer cell lines, confirmed by a morphological study of treated and untreated colon cancer cell lines and the acridine orange/ethidium bromide (AO/EB) dual staining procedure, respectively. After 48 hours of incubation with respective IC₅₀ concentrations of MEPJB, the treated colon cancer cells showed early and late apoptotic features. So this current research work indicates that the methanolic extract of P. javanica bark has chemotherapeutic potential against colon cancer cells and promotes apoptosis in cancer cells, which results in cell death.